PENGARUH AKTIFITAS FISIK DAN CEMAS TERHADAP AKTIVITAS SEKSUAL PADA IBU MENOPAUSE DI KECAMATAN MUARA DUA KOTA LHOKSEUMAWE - Nurmila, Nurmila; Jasmiati, Jasmiati; Elizar, Elizar (Universitas Murni Teguh, 2021)
The decline as the effect of menopause will cause the decline in various body system, including the decline in mothers’ sexuality. It can happen when there are physical change, psychological change, the lack of information and knowledge of the change in mothers, and people’s negative perception on sexuality in old age. The objective of the research was to analyze factors physical activit, and apprehensiveness, which influenced sexual activity of menopause mothers in Muara Dua Subdistrict, Lhokseumawe. The research used observational method with cross sectional design. The population was all menopause mothers who still had spouses and lived in Muara Dua Subdistrict, and 82 of them were used as the samples. The data were analyzed by using univatriate analysis, bivatriate analysis. The result of the research showed that of 82 respondents, 56.1% of them were not sexually active. The result of chi square statistic test showed that the variables of physical activities and apprehensiveness (p < 0.001). It is recommended that menopause mothers should keep the health and bodies fresh, decrease physical activities by cooperating with families, especially husbands and should be willing to tell about sexuality in the menopause period to decrease apprehensiveness. Mothers and their husbands should have good perception on sexual activity during menopause so that they can increase their sexual life during menopause. Abstrak Kemunduran akibat masa menopause akan membawa dampak pada penurunan berbagai sistim tubuh termasuk penurunan seksualitas ibu. Penurunan seksualitas pada ibu menopause dapat terjadi karena adanya perubahan pada fisik. Jenis penelitian adalah observasional dengan pendekatan Cross-sectional. Penelitian ini bertujuan menganalisis hubungan aktivitas fisik dan cemas terhadap aktivitas seksual pada ibu menopause. Populasi pada penelitian ini adalah semua ibu menopause yang ada di kecamatan Muara Dua sebanyak 544 orang. Sampel dalam penelitian ini diambil berdasarkan rumus Lameshow dengan jumlah sampel 82 orang. Analisis data menggunakan analisis univariat, analisis bivariat dengan uji Chi-squre. Hasil penelitian dengan uji Chi-square menunjukkan hasil bahwa aktivitas fisik dan cemas sangat berpengaruh terhadap aktivitas seksual yaitu (p < 0,001). Disarankan kepada tenaga kesehatan terutama bidan dan perawat yang bertugas di Puskesmas terutama saat kegiatan di luar gedung agar dapat melakukan komunikasi, memberikan informasi dan edukasi terutama tentang aktivitas seksualitas masa menopause.